Pengaruh Sistem Informasi Akuntansi dan Kualitas Pengambilan Keputusan terhadap Kinerja Manajerial pada Instalasi Gizi di RSUD Dr. Soetomo Provinsi Jawa Timur - Prisca Ambarwati; J. B. Amiranto (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of accounting information systems and decision-making quality on managerial performance in the Nutrition Installation Unit at RSUD Dr. Soetomo, East Java Province. The research background highlights the critical need for accurate and timely information to support managerial functions, especially in strategic hospital units such as nutrition services. A quantitative associative method was applied, using purposive sampling to select 30 respondents from a total population of 136 employees. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 23. The results show that both the accounting information system and decision-making quality have a positive and significant partial influence on managerial performance. Simultaneously, these variables also significantly affect managerial performance. The findings reinforce the importance of implementing an integrated accounting information system and high-quality decision-making processes to enhance managerial performance within hospital environments.